Etnografi Pengenalan Kuliner Khas Aceh Bagi Mahasiswa di Kota Kendari: Pengabdian - La Ode Aris; Laxmi; Siti Hermina; Subandrio; Adhe Ismail Ananda (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This community service activity aims to determine the forms of activities and initiatives undertaken by the association to preserve Acehnese values, traditions, and culinary delights among migrants in Kendari City, and to understand the mechanisms and activities carried out by the association to strengthen bonds of solidarity, social cohesion, and build networks among fellow migrants from Aceh in Kendari. The background to this activity stems from the fact that the presence of regional associations in migration destination cities such as Kendari plays a vital role in the lives of migrants. The functions of associations are very diverse, ranging from strengthening bonds of brotherhood, helping newcomers adapt to their new environment, to preserving and promoting cultural values of their region of origin. This activity involved observation, interviews, training, and technical assistance within the Aceh association. The results of the activity showed that the culinary delights of the association can attract the attention of the local community in Kendari. The diverse culinary delights served at the association can attract customers who want to experience the unique culture. For example, as the name suggests, teh tarik can attract the attention and interest of customers. Associations are often a symbol of community strength. Culinary arts can foster a sense of belonging to a particular region or community.